Plant-Based Milks: Cashew - Jamie Zeldman; Daniela Rivero-Medoza; Wendy J Dahl (EDIS)
The availability and consumption of plant-based milk alternatives have been on the rise. Sales of nondairy milk alternatives have more than doubled, whereas consumption of traditional cow's milk has dropped.  This increase may be due to plant-based milks being perceived as "natural," as well as a rise in veganism and avoidance of lactose. The primary plant-based dairy alternatives are almond, soy, coconut, cashew and rice. This new 4-page publication of the UF/IFAS Food Science and Human Nutrition Department discusses the nutritional content, potential health benefits, and potential risks of cashew milk. Written by Jamie Zeldman, Daniela Rivero-Medoza, and Wendy J. Dahl. https://edis.ifas.ufl.edu/fs413